Cultural diversity and plant-level productivity - Michaela Trax; Stephan Brunow; Jens Südekum (Institute for the Study of Labor (IZA), 2012)
Using comprehensive data for German establishments (1999-2008), we estimate plant-level production functions to analyze if cultural diversity affects total factor productivity. We distinguish diversity in the establishment's workforce and in the aggregate regional labor force where the plant is located. We find that a larger share of foreign workers - either in the establishment or in the region - does not affect productivity. However, there are strong spillovers associated with the degree of cultural heterogeneity. The aggregate level is, quantitatively, at least as important as the workforce composition inside the establishment. Diversity thus seems to induce externalities beyond the boundaries of a single firm; it improves local business environments.
Keywords: R23; J21; J31; 330; cultural diversity; plant-level productivity; knowledge spillovers; Produktivität; Unternehmen; Multikulturelle Gesellschaft; Wissenstransfer; Deutschland